Adsorpsi Anion Nitrat Menggunakan Silika Gel (SiO2) GPTMS Dimodifikasi dengan Dimetilamina - Anisa Nahari; Budhi Oktavia; Miftahul Khair; Ananda Putra (Departemen Kimia FMIPA UNP, 2022)
Silica or silicon dioxide is a chemical compound with the molecular formula SiO2 which can be obtained from the synthesis of crystals, silica minerals, and vegetables. Compounds resulting from the polymerization of silicic acid, which are composed of a tetrahedral SiO4 unit chain with the general formula SiO2. Each silica atom is surrounded by four oxygen atoms. Silica forms a polyhedral network, where the bonds between oxygen tetrahendral are one and the other. Silica will form a framework that has pores that are quite open and allow other molecules to enter and undergo adsorption on the surface of the silica. Modification of silica is done by adding heat at a certain temperature, adding reagents to the active site of silica will change the silica functional group. Silica with the addition of amine compounds reacted with GPTMS can be used as nitrate anion adsorption to see the absorption capacity of silica against nitrate anions using the batch method. The factors used to see this adsorption capacity include pH at pH 7 with an absorption of 1.931463 mg/g and the percentage of absorption is 79.5%. and contact time with a time of 90 minutes with an absorption of 0.32677 mg/g and the percentage of absorption is 67.28785%.